The Effectiveness of Canva Media on the Learning Outcomes of Class V Students of Madrasah Ibtidaiyah Norm Material in Life - Farihah, Fadhilah Fitriawati; Utami, Ratnasari Diah (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study investigates the effectiveness of Canva as a learning medium for teaching the “norms in life” topic within Pancasila Education to fifth‑grade students at Madrasah Ibtidaiyah Sudirman Ceplukan, with the goal of determining whether digital visual tools can enhance comprehension and retention compared to conventional instruction. Methodology: A quasi‑experimental quantitative design was employed, involving two intact classes: Class V A (control) received traditional lecture‑and‑discussion lessons, while Class V B (experimental) engaged with Canva‑based presentations, infographics, and interactive exercises. Researchers validated a multiple‑choice test for reliability and then administered pretests and posttests. Data analysis included checks for normality and homogeneity, descriptive statistics, independent‑samples t‑testing to compare posttest means, and normalized gain (N‑gain) calculations to assess learning gains. Results: The control class achieved an average posttest score of 71.20, whereas the experimental class scored 85.40. The independent‑samples t‑test yielded a significance value of 0.000 (p < 0.05), indicating a statistically significant improvement in the Canva group. Moreover, the experimental class’s N‑gain of 0.604 (60.46%) falls into the “quite effective” category, demonstrating that Canva media substantially boosted student learning outcomes over traditional methods. Applications/Originality/Value: By providing empirical evidence of the impact of visually rich, digitally interactive content on student achievement, this study offers a practical model for Pancasila Education and other social‑studies subjects. Educators can leverage Canva to craft engaging materials that cater to diverse learning styles and foster deeper conceptual understanding. These findings advocate for integrating accessible design tools into elementary curricula to promote higher engagement and learning efficacy.